Mineral content of the natural range in southern Brazil. I. Calcium, phosphorus, magnesium and potassium - Senger, Clóvis Cleno Diesel; Sanchez, Luis Maria Bonnecarrére; Pires, Maria Beatriz Gonçalves; Kaminski, João (Pesquisa Agropecuaria Brasileira, 1996)
Samples of soil and natural range forrage were collected from eleven different soil classes in Rio Grande do Sul, Brazil, to determine concentration of several minerals and compare them with beef cattle requirements. Soil samples were taken just once, in the spring of 1989, and pasture samples were collected during five seasons, from the spring of 1989 to the spring of 1990. The average mineral content for the different soil classes was greater than 4.0 me/1 00 ml for Ca, ranging from 3.0 to 4.6 ppm for P, and 3.5 and 17.2 me/100 ml for Mg; K content was higher than 46.7 ppm. The average mineral content of pastures from the different soil classes varied from 0.32 to 1.20% for Ca; 0.06 to 0.19% for P; 0.06 to 0.15%for Mg, and from 0.44to 1.81% forK. Ninety eightpercentof the pastures presented P content lower than the beef cattle requirements (0. 18%); 16.4 and 14.5% respectively, presented contents of K and Mg lower than the requirements. The Ca levels were sufficient to supply the beef cattle needs.